The Effect of Modified Learning Cycle Strategy (7E’S) On the Achievement of Grammatical Concepts of Kurdish Language among Fifth-Literary Stream Secondary School Female Students. - Abdul Kareem Ahmed, Mahabad (Al-Adab Journal, 2021)
The Effect of modified learning cycle strategy (7E’S) on the achievement of grammatical concepts of Kurdish language among fifth-literary stream secondary school female students. The sample amounted (63) female students distributed on two sections (A، B). Section A represented experimental group (31) female students studied according to the exemplar of (Modified Learning Cycle Strategy (7E’S) and (B) represented control group (32) female students who have studied with traditional method. The researcher has qualified between these two groups based on coefficients (age، intelligence، marks of the first course). The scientific subject has been determined by many grammars’ subjects in the book ((Zaman Waa Dah Bi Kurdish)) decided to be studied in basic 7th class. The researcher has formed behavior goals and has prepared teaching plans sufficient for these two groups، she has also prepared a test to acquire grammatical concepts، composing of (24) items by which the teacher has taught the two groups. By the end of the experience، tool of research has been applied on students of both groups. After analyzing the result statistically by using (T-test) for the two independent samples، the results have indicated the progress of experimental group studying Grammar Subject according to the method of (Modified Learning) Cycle Strategy (7E’S) over the control one.